2019
DOI: 10.4236/me.2019.102023
|View full text |Cite
|
Sign up to set email alerts
|

Empowerment of Youth Agribusiness Entrepreneurs Using Social Capital Based Business Models Canvas in North Sulawesi

Abstract: The purpose of this study was to engineer a social capital-based canvas business model that is oriented towards the value of products offered to customers and devised a strategy to empower young entrepreneurs to develop their business in Manado, North Sulawesi, in 2018. ANP (analytical network process) analysis was chosen as a decision analysis tool engineer of this business system. ANP allows dependencies and feedback, both between elements in the cluster (inner dependence) and between clusters (outer depende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Ramasobana et al (2017) argued that owners of MSEs enter into economic activities because they not only need financial incentives, family culture acting as a role model, and independence to be their own's bosses but they also need to utilize their skills acquired. Merung et al (2019) have observed that youth entrepreneur characteristics positively contribute to the growth of enterprises. The authors indicated previous experience and education level as the main elements that enable young entrepreneurs to bring their businesses to success.…”
Section: Market Access and Growth Of Youth-owned Msesmentioning
confidence: 99%
“…Ramasobana et al (2017) argued that owners of MSEs enter into economic activities because they not only need financial incentives, family culture acting as a role model, and independence to be their own's bosses but they also need to utilize their skills acquired. Merung et al (2019) have observed that youth entrepreneur characteristics positively contribute to the growth of enterprises. The authors indicated previous experience and education level as the main elements that enable young entrepreneurs to bring their businesses to success.…”
Section: Market Access and Growth Of Youth-owned Msesmentioning
confidence: 99%
“…Merung, Darmawan, Windia and Astiti (2019) drew on the analytical network process (ANP) model to assess how Indonesian youths could be empowered to become pragmatic entrepreneurs in agribusiness. Merung et al (2019) relied on the social capital-based business model canvas (SCBMC) to examine the value of products offered to customers. Indonesia is an agrarian economy.…”
Section: Policies and Strategies For Agribusiness And Agricultural Sector Developmentmentioning
confidence: 99%
“…Another factor in line with this is shown by the results of a survey from the Indonesian Political Indicator and the Bright Indonesia Foundation, namely that 53% of Indonesia's young generation are worried about environmental damage. These things, among others, encourage the livestock industry, especially fresh milk industry, to carry out green supply chain management optimally [2], [3].…”
Section: Introductionmentioning
confidence: 99%